Cs+ ion exchange over lanthanide silicate Eu-AV-20: Experimental measurement and modelling - Figueiredo, Bruno R
The ion exchange of Cs+ from aqueous solutions was studied using for the first time a microporous lan thanide silicate with photoluminescence properties, Eu AV 20. It was prepared by hydrothermal synthe sis, characterized by SEM, PLS, PXRD and ICP MS, and several batch ion exchange experiments were performed to measure isotherm and removal curves. Additional curves were measured to evaluate the competition with Na+. The results evidenced the great selectivity of Eu AV 20 towards Cs+ since cesium removal was slightly modified even for Na+/Cs+ concentrations ratio of 190. The emission photolumines cent spectra of native and Cs+ exchanged Eu AV 20 were also determined for the first time, and signifi cant modifications were detected, which discloses the potential of Eu AV 20 for Cs+ sensing purposes. The Langmuir equation provided a good fit to the equilibrium data, with average error of 5.3%, and the Maxwell Stefan based model adopted to represent the kinetic curves (i.e., concentration versus time) achieved a deviation of 19.0%. An analysis of variance confirmed that the model was statistically signif icant to represent the uptake curves. The Maxwell Stefan based model comprises three parameters, namely, the diffusion coefficients asso ciated to the interactions of Cs+ and Eu AV 20, Na+/K+ and Eu AV 20, and Cs+ and Na+/K+, whose fitted values were 2.706 10 15, 5.713 10 15 and 9.446 10 17 m2 s 1. Such low values evidenced that the intraparticle mass transport mechanism is surface diffusion. This fact is ascribed to the small pores of the Eu AV 20 crystal, 5.8 6.8 Å, because the counter ions never escape from the force field of the framework co ions, mainly due to the strong and long range nature of the electrostatic interactions.